ANALISIS MINAT PENGUNJUNG YANG BERWISATA KE GALERI NASIONAL INDONESIA - Nasution, Deivy Zulyanti; Alexandra, Cut Meutia; Fitriana, Rina (Jurnal Ilmiah Pariwisata, 2019)
Tourism in Indonesia is increasing every year. The Special Capital Region of Jakarta or DKI Jakarta is the capital of the Republic of Indonesia. DKI Jakarta offers a variety of tourist destinations for all walks of life, from family attractions, nature, culture, education, to culinary. One type of tourism that is quite attractive in DKI Jakarta is cultural tourism. Tourists visit certain places with the aim of learning about the cultural appeal or utilizing the cultural potential of the places visited. The types of art activities consist of performance arts, exhibitions, collections of paintings, and other artistic activities. One of the tourist attractions in DKI Jakarta that has various art collections and holds exhibitions is the National Gallery of Indonesia. This study aims to determine the interest of visitors who travel to the National Gallery of Indonesia. This study uses descriptive research methods with quantitative approaches. Data collection uses a questionnaire whose results will be processed using Microsoft Excel software.The results of this study obtained a value of 3.83 where this value indicates that the interest of visitors who travel to the National Gallery of Indonesia is High.